A tattoo-inspired electrosynthesized polypyrrole film: crossing the line toward a highly adherent film for biomedical implant applications - Borges, M. H.R.; Nagay, B. E.; Costa, R. C.; Sacramento, C. M.; Ruiz, K. G.; Landers, R.; van den Beucken, J. J.J.P.; Fortulan, C. A.; Rangel, E. C. [UNESP]; da Cruz, N. C. [UNESP]; Barão, V. A.R. (Elsevier, 2022)
Polypyrrole (PPy) films have demonstrated promising application for implants due to their unique topographical and electronic properties. However, the limited PPy adhesiveness to metallic surfaces remains a challenge. Consequently, we propose a two-step technique for the surface modification of titanium (Ti) via a plasma electrolytic oxidation (PEO) step to serve as mechanical interlocking for the subsequent deposition of a highly adherent PPy film (PEO + PPy). Ti discs with machined and PEO-modified surfaces were used as controls. For the experimental groups, PPy film was deposited onto such surfaces by electrodeposition. Then, the role of machined and PEO surfaces in the synthesis, conductivity, microstructure, mechanical, electrochemical, microbiological, and biological properties of the PPy film was investigated. The results showed that a highly adherent “tattoo-inspired” PPy thin film was successfully achieved when the Ti surface was pretreated via PEO. PEO + PPy enhanced Ti mechanical and tribological properties by inducing a lower friction coefficient and wear loss due to the cushion effect of PPy film, besides promoting higher corrosion resistance. The “cauliflower-like” morphology of the PPy favored protein adsorption, calcium phosphate growth and demonstrated cell biocompatibility. The association between PEO and PPy film can be considered bioactive and is promising for the triggering of superior long-term stability of biomedical implants.
Keywords: Corrosion; Dental implants; PPy; Surface treatment; Titanium